The Potency of miRNA 221-3p as a Molecular Biomarker Of Temporomandibular Disoder: Narrative Review - Rintoko, Bimo; Tanti, Ira; Bachtiar, Endang Winiati; Bachtiar, Boy Muchlis; Prihastari, Lisa (Odonto : Dental Journal, 2025)
United States. The trigeminal nerve might be the source of orof facial pain. Pain can be difficult to diagnose and treat due to the variability of pain complaints. miRNA 221-3p could be a potential biomarker for pain. Genetic polymorphisms and genetic mutations can lead to changes in the activity of inflammatory mediators, sex hormones, matrix-degrading enzymes, and the immune system, which affect bone remodeling homeostasis in the temporomandibular joint.Method: Scientific databases PubMed, Scopus, and Google Scholar were searched for articles published between 2013 and 2023 in order to conduct the study. 168 carefully selected publications providing information on possible biomarkers, particularly miRNA 221-3p, were included in the review of the literatureResult: Genetic polymorphisms and genetic mutations can lead to changes in the activity of inflammatory mediators, sex hormones, matrix-degrading enzymes, and the immune system, which affect bone remodeling homeostasis in the temporomandibular joint. In addition, activity changes were also observed in neurotransmitters and pain receptors, which resulted in relatively high pain sensitivity. Thus, this condition also increases susceptibility to TMD. Genetic analysis and biomarkers of temporomandibular disorders may improve sensitivity and specificity measures in diagnosing and treating patients with TMDConclusion: As a multifactorial disease, genetic factors are risk factors for TMD. Genetic polymorphisms and genetic mutations can lead to changes in the activity of inflammatory mediators, sex hormones, matrix-degrading enzymes, and the immune system, which affect bone remodeling homeostasis in the TMD